NGF promotes mouse granulosa cell proliferation by inhibiting ESR2 mediated down-regulation of CDKN1A. (5th May 2015) - Wang, Yong; Liu, Wenjing; Du, Juan; Yu, Yang; Liang, Ning; Liang, Meng; Yao, Guidong; Cui, Sheng; Huang, Hefeng; Sun, Fei
Highlights: NGF promote GC proliferation through trkA. CDKN1A mediates NGF-stimulated GC proliferation in a TRP53-independent manner. The involvement of CKDN1A on NGF-induced GC proliferation is regulated by trkA and ERK1/2. The effect of CDKN1A on NGF-induced GC proliferation is mediated through ESR2. ESR2 may be a potential regulator of CDKN1A and NGF signaling in GC proliferation. Abstract: Nerve growth factor (NGF) is known to play key roles in ovarian follicular development, such as the assembly of early follicles and follicular ovulation through its high-affinity receptor, tyrosine kinase receptor A (trkA). Herein, the molecular mechanism controlling NGF-induced granulosa cell (GC) proliferation was not clear. In this study, we found that NGF is abundant in preantral GCs and knockdown of trkA in GCs attenuated NGF-induced GC proliferation and further decreased the levels of phosphorylated extracellular regulated protein kinases 1/2 (ERK1/2). Cyclin-dependent kinase inhibitor 1A (CDKN1A), also named p21, a factor which could be either a negative or a positive regulator via transformation related protein 53 (TRP53, also named p53)-dependent or independent pathways in cell proliferation, was up-regulated during the process of NGF-induced GC proliferation. Blockade of trkA (K252α) and ERK1/2 (U0126) in GCs decreased NGF-induced expression of CDKN1A and did not alter the expression of TRP53, indicating that NGF stimulates CDKN1A expression via the trkA-ERK1/2 pathway in a TRP53-independent manner. Meanwhile, ESR2, a tumor suppressor which is exclusively expressed in GCs, was suppressed in NGF-induced GC proliferation, and this effect was abrogated by U0126. Blockade of ESR2 (ICI182, 780) caused the promotion of GC proliferation and CDKN1A expression, indicating that ESR2 may be downstream of the ERK1/2 pathway in mediating the effect of CDKN1A on NGF-induced GC proliferation. Therefore, ESR2 may be involved in the integration of intracellular signal cascades and cell cycle proteins in affecting GC proliferation. Here, we provide mechanistic insights into the roles of CDKN1A in NGF-induced GC proliferation. Understanding potential cross-points between CDKN1A and ESR2 affecting GC proliferation will help in the discovery of new therapeutic targets in some female infertility disorders.